ANALISA EKSTRAK ETANOL DAUN BAJAKAH KAIT-KAIT (Uncaria acida (Hunt.) Roxb.) TERHADAP BAKTERI Escherichia coli MENGGUNAKAN METODE KIRBY BAUER - Mia Irawan; Febri Nur Ngazizah; Riky Riky; Iqlila Romaidha (Asosiasi Institusi Pendidikan Tinggi Teknologi Laboratorium Medik Indonesia, 2021)
Kalimantan forest is the largest tropical rain forest which is one of the places with biodiversity that has the potential for development in the field of health or medicine, one of the plants used for treatment is hook root (Uncaria acida (Hunt.) Roxb.). This plant has indole alkaloid compounds, triterpenes, flavonoids and phenylpropanoids that act as antibacterial. In this study, an antibacterial test was conducted using the Kirby Bauer method to determine the antibacterial activity which was characterized by the formation of an inhibition zone around the paper disc. The bacteria tested were E. coli. The extract tested in this study was the ethanolic extract of U. acida leaves with 5 concentrations of treatment (5 mg/mL, 15 mg/mL, 30 mg/mL, 40 mg/mL and 50 mg/mL). The average result of the inhibition zone of the ethanolic extract of U. acida leaves in a concentration of 5 mg/mL is 8.1 mm in the weak category, the concentration of 15 mg/mL is 8.3 mm in the weak category, the concentration of 30 mg/mL is 9.1 mm in the weak category, 40 mg/mL ie 9.2 mm in the weak category and 50 mg/mL in the moderate category. Using significance (? > 0.05) which means that the inhibition zone data on the growth test of E. coli bacteria at the 5 concentrations affected the inhibition zone of E. coli bacteria.